MRI after implantation of a novel femoral closure device following intra-arterial catheterisation: implications for subsequent contrast-enhanced MR angiography - Mohrs, Oliver K.; Petersen, Steffen E.; Nowak, Bernd; Kauczor, Hans-Ulrich; Voigtlaender, Thomas (European radiology, 2010)
To assess MRI safety aspects and artefacts of a novel femoral artery closure device during contrast-enhanced MR angiography in patients following intra-arterial catheterisation.